Diversity And Inclusion In Indian Workplaces: Policies, Practices And Outcomes - Dr Madhura Shukla (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Diversity and inclusion (D&I) have gained prominence as critical factors for organizational success and employee well-being in contemporary workplaces. This research paper explores the landscape of D&I within Indian workplaces, focusing on the effectiveness of policies, implementation practices, and their resultant outcomes. Through a comprehensive literature review and empirical analysis, the study examines the evolution of D&I initiatives, the influence of cultural and societal factors on their adoption, and their impact on organizational performance and employee engagement. Key findings highlight the challenges and opportunities in promoting D&I in India, including regulatory frameworks, leadership commitment, employee perceptions, and the role of HR practices. The paper concludes by discussing implications for future research and practical recommendations for fostering inclusive workplaces that celebrate diversity across various dimensions.